KEARIFAN LOKAL PADA KOMUNITAS ADAT KEJAWEN BONOKELING - Arnis Rachmadhani (Harmoni, 2015)
This is a qualitative research that is conducted in Kejawen (indigenous tradition in Java) communities in Pekuncen village, Jatilawang district, Banyumas regency. Data is collected by using interviews, observation, and documentation. This research describes the spread of traditional Javanese by Kyai Bonokeling which has variety of rituals such as unggahan and udunan that can be an inspiration for building or strengthening faith in religious harmony. Unggahan or sadran activities describe a preparation conducted by farmers in facing rice planting season, while turunan activities represent a symbol of gratitude in having rice harvest season. Unggahan or sadran activities also have meaning to face the fasting month and turunan is as a sign of completion.